Taxonomical entities of the Chotoy spinetail Schoeniophylax phryganophilus : (Aves: furnariidae) at the Paraná river floodplain, Argentina - Alessio, Viviana; Beltzer, Adolfo (UNIVERSIDAD ANTONIO NARIÑO, 2009)
The objective of this research was to study the barely known taxonomical entities of passerine Chotoy spinetail —Schoeniophylax phryganophilus— at the Paraná River floodplain, with the purpose of giving quantified data about trophic spectrum and diversity, circadian rhythm, habitat selection, niche amplitude, and prey size.